Probability of rainfall-induced landslides coupled with effective-duration threshold and soil moisture - Kailiang Zhao; Haijun Qiu; Ya Liu; Zijing Liu; Wenchao Huangfu; Bingzhe Tang; Dongdong Yang; Guoqing Yang (Journal of Hydrology: Regional Studies)
Study region: Shaanxi Province, including the Loess Plateau in northern Shaanxi, the Guanzhong Plain, and the Qinba Mountains in southern Shaanxi. Study focus: Frequent extreme rainfall exacerbates the risk of rainfall-induced landslides, highlighting the importance of rainfall thresholds quantification for accurate hazard prevention. New hydrological insights for the region: The rainfall on the day and 7–28 cm soil moisture have a strong impact on landslide occurrences. The effective duration threshold for rainfall-induced landslides is largest in the Qinba Mountains area (high vegetation cover), and the 50 % threshold curve has a better early warning effect. Under high soil moisture and rainfall conditions, the probability for rainfall-induced landslides increases. In contrast, the probability threshold for landslides in areas with high vegetation coverage is also higher. This study quantified the probability thresholds for rainfall-induced landslides based on the coupled effective duration threshold and soil moisture. The results provide a theoretical reference for the precise prevention of landslides.